Development of Sensory Mat Learning Media to Train Motor Skills at TK IT Kautsar Ilmi Tanjung Raja - Amelia, R.A; Amilda, Amilda; Putri, Yecha Febrieanitha; Febriyanti, Febriyanti (Al-Mudarris, 2024)
This study was motivated by the ability of motor movement in IT Kautsar Ilmi Kindergarten Tanjung Raja, Ogan Ilir Regency, which has not developed optimally. This is due to the limited learning media used by teachers, so that children are less interested and do not get direct experience in learning. This study aims to develop a valid and practical Sensory Mat media to train motor skills in the kindergarten. The research method uses Research and Development with the ADDIE model, namely Analysis, Design, Development, Implementation, and Evaluation. The research subjects were group B at IT Kautsar Ilmi Tanjung Raja Kindergarten, with an initial trial in the Ar-Rahman class of 10 students and the main trial involving the entire group B of 19 students. Data were collected through observation, questionnaires, documentation, and interviews, then analyzed using validity and practicality tests with a Likert scale. The validation results showed that the material expert's score was 80 with a very valid category and the media expert was 96.67 with a very valid category. Practicality test based on teacher questionnaire reached 100 with a very practical category. Students' responses showed a value of 75.68 declared practical in the initial trial and 92.35 declared very practical in the main trial. This study concludes that Sensory Mat media is effective, valid, and practical for training children's motor skills at IT Kautsar Ilmi Tanjung Raja Kindergarten.